Adrenalectomy for primary aldosteronism and its related surgical characteristics - Xiang, Hao; Zhang, Tingting; Song, Wei; Yang, Deyong; Zhu, Xinqing (Frontiers in Endocrinology, 2024)
Primary aldosteronism (PA) is a common cause of secondary hypertension. Adrenalectomy is an effective treatment for unilateral PA, particularly aldosterone-producing adenoma (APA), resulting in improvements in biochemical parameters and blood pressure in the vast majority of patients. The article provides a comprehensive overview of PA, focusing on the outcomes of adrenalectomy for PA and the factors that may suggest prognostic implications. Analysis of the outcome of different PA patients undergoing adrenalectomy in terms of preoperative factors, vascular and adipose conditions, type of pathology, and somatic variants. In addition, it is recommended to use the histopathology of primary aldosteronism (HISTALDO) consensus to classify the patient's pathological type, with classical and nonclassical pathological types showing a different prognosis and possibly being associated with an unresected contralateral adrenal gland. The primary aldosteronism surgical outcome (PASO) consensus sets uniform standards for postoperative outcomes in unilateral PA, but its setting of thresholds remains controversial. Partial adrenalectomy shows similar surgical results and fewer postoperative complications than total adrenalectomy, but there is a risk of missing the true source of abnormal aldosterone secretion. Steroid profiling and functional imaging techniques offer alternative options to adrenal vein sampling (AVS) for unilateral and bilateral judgments in patients with PA. A combination of factors is needed to predict the prognosis of PA patients undergoing adrenalectomy in order to manage patient expectations of the outcome of the procedure and to closely monitor blood pressure and biochemical parameters in patients who suggest a poorer prognosis.